2022
DOI: 10.1155/2022/2869707
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Protective Effect and Mechanism of the Rhizoma Drynariae‐Epimedium Formula on Osteoarthritis in Rats

Abstract: Purpose. The aim of the study was to study the protective effect of the Rhizoma Drynariae-Epimedium formula on osteoarthritis in rats and to explore its mechanism. Methods. Fifty SD rats were randomly divided into 5 groups, namely, the control group, model group, Rhizoma Drynariae group, Epimedium group, and Rhizoma Drynariae-Epimedium group, with 10 rats in each group. Knee arthritis models were established by injecting papain solution (10% papain + 0.03 mol/L L-cysteine mixture) into the knee joint cavity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The swelling degree of knee joint of rats was observed by measuring the diameter of the right knee joint of rats in each group using an electronic caliper 22 .…”
Section: Monitoring Of the Movement Trajectory And Number Of Stands O...mentioning
confidence: 99%
“…The swelling degree of knee joint of rats was observed by measuring the diameter of the right knee joint of rats in each group using an electronic caliper 22 .…”
Section: Monitoring Of the Movement Trajectory And Number Of Stands O...mentioning
confidence: 99%
“…Discussion. As mentioned above, EF is widely used in clinical practice with signifcant pharmacological efects [18,19,21,23]. Nonetheless, there are a limited number of comprehensive studies on the quality of EF both domestically and internationally, particularly articles that provide a comprehensive analysis of the bioactive constituents of various species.…”
Section: Gra Of Samples Grey Correlation Degree Analysismentioning
confidence: 99%
“…Te research showed that EF contains a variety of bioactive constituents, but not limited to favonoids [9,11], phenolic acids [12], volatile oil [13], polysaccharides [14,15], nucleic acid, amino acids, alkaloids, and lignans [16,17]. Tese bioactive constituents play a signifcant role in the exceptional clinical function, such as antiosteoporosis [18], bone repair [19,20], hormone-like efects [21], antitumor [22], anti-infammatory [23], antiaging [24], immunomodulation [15,25], and treatment of cardiovascular and cerebrovascular diseases [26,27]. Flavonoid glycoside derivatives with 8-isopentenyl favonol as the basic mother nucleus, represented by icaritin and icariin, have been proved to be the main substances that exert the above pharmacological efects.…”
Section: Introductionmentioning
confidence: 99%